Kualitas Pelayanan Rawat Inap Rumah Sakit Umum Batara Siang Kabupaten Pangkep - Sulfiah, Andi; Mappamiring, Mappamiring; Mone, Ansyari (Universitas Muhammadiyah Makassar, 2020)
This study aimed to determine how the Quality of the hospitalizations in Batara Siang General Hospital, Pangkep Regency. This study used qualitative research and the type of research used descriptive qualitative research. Data sources were primary data and secondary data. The number of informants in this study were 7 people. Data collection techniques user observation, interview, and documentation techniques. Data analysis techniques used data reduction, data presentation and conclusions. The result of this study could be seen that the Quality of the hospitalizations Services of the Batara Siang Public Hospital in Pangkep Regency showed that the improvement of public service still needed to be improved so that Human Resources in Batara Siang General Hospital in Pangkep Regency was better, more effective, faster and more efficient. There were improvements in improving services made by the governments in public services were expected always fasilitate public services for the community.